Lingkungan Fisik Rumah Pada Baita Penderita ISPA - Haryani, Haryani; Thoyibah, Zurriyatun; Hajri, Zuhratul; Hardiani, Sri (Jurnal Ilmiah STIKES Yarsi Mataram, 2020)
Acute Respiratory Infection (ARI) is one of the health problems in develoving countries because of the high morbidity and mortality due to ARI in children under five. ARI is included in the top 10 disease category in NTB with the highest number of visits 174,213. There are 3 risk factors for ARI, namely enviromental factors, individual child factors dan behaviors factors. This study aims to describe the physical enviroment of the toddler’s home with ARI. This research is a descriptive study with a cross-sesctional study design. The sample size is 20 mother who have toddler aged 0- 59 months who experience ARI. Collecting data using physical environtment obeservation sheet and signs of ARI symptoms. The results showed that almost all of the ventilation, house temperature and occupancy density did not meet health requerements, namely as many as 85%-95% of respondents. Most of the respondents house humidity did not meet the requerements as much as 75%, as much as 95% used traditional cooking fuels and most of the use of mosquito reppelent did not meet health requerements (70%), and most of the respondent smoked indoors (60%). It can be concluded that the behaviour and physical environment of the home of toddlers who suffer from ARI mostly does not meet the health requerements.